The role of social norms in zero price effects - Xian Zhang; Tom Lane; Jose M. Grisolia (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
It has been proposed that social norms play a role in zero price effects on consumption. In Study 1, we use a norm-elicitation experiment to directly measure the effects on norms of consumption, demonstrating that the social appropriateness of consuming high quantities is significantly lower when goods are offered for free than when they are sold at 1 cent. In Study 2, we employ a natural field experiment to put into practice the scenarios from Study 1 and measure actual consumption behavior. Results depend upon how we measure zero price effects, but offer some support for findings of previous research that zero pricing increases the likelihood of an individual consuming while reducing the amount taken by those who do consume. Overall, the evidence suggests high consumption of free goods is prevented by its social inappropriateness, potentially helping to explain for the inconsistent evidence on the direction of zero price effects in previous studies. Conditional logit estimations suggest social norms drive consumption decisions for free goods, while material benefits are the dominant consideration when goods are positively priced.
Keywords: 330; social norms; social appropriateness; zero price effects; natural field experiment; norm-elicitation task